2020
DOI: 10.1183/23120541.00302-2020
|View full text |Cite
|
Sign up to set email alerts
|

Do probiotics help prevent ventilator-associated pneumonia in critically ill patients? A systematic review with meta-analysis

Abstract: BackgroundProbiotic treatments might contribute to the prevention of ventilation-associated pneumonia (VAP). Due to its unclear clinical effects, here we intend to assess the preventive effect and safety of probiotics on Intensive Care Unit (ICU) patients.MethodsEligible randomised controlled trials were selected in databases until 31 September 2019. The characteristics of the studies were extracted, including study design, definition of VAP, probiotics intervention, category of included patients, incidence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 60 publications
2
32
0
Order By: Relevance
“…However, our results demonstrated that the use of probiotics could reduce the length of ICU stay, duration of mechanical ventilation, and incidence of bacteria colonization. Compared with previous meta-analyses by Zhao et al (13) and Ji et al (12), the trials by Klarin et al (36) and Kotzampassi et al (37) were excluded in our meta-analysis because the patient cohorts of these two trials are the same as in Klarin et al (19) and Giamarellos-Bourboulis et al (29). Furthermore, our meta-analysis included the latest study by Johnstone et al (16), which enrolled more than 2,600 patients and was the largest randomized trial to date.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…However, our results demonstrated that the use of probiotics could reduce the length of ICU stay, duration of mechanical ventilation, and incidence of bacteria colonization. Compared with previous meta-analyses by Zhao et al (13) and Ji et al (12), the trials by Klarin et al (36) and Kotzampassi et al (37) were excluded in our meta-analysis because the patient cohorts of these two trials are the same as in Klarin et al (19) and Giamarellos-Bourboulis et al (29). Furthermore, our meta-analysis included the latest study by Johnstone et al (16), which enrolled more than 2,600 patients and was the largest randomized trial to date.…”
Section: Discussionmentioning
confidence: 88%
“…They can selectively modulate the growth of the microbiome, inhibit colonization with invasive pathogens, and improve the microecological balance of the host (9). Recent meta-analyses (10)(11)(12)(13) indicated that the administration of probiotics could significantly reduce the incidence of VAP. However, several studies have described the potential risks of probiotics such as systemic infections, deleterious metabolic activities, excessive immune stimulation in susceptible individuals, gene transfer, and gastrointestinal side effects (14,15).…”
Section: Introductionmentioning
confidence: 99%
“…Understanding how particular species-and/or strain-level functional differences in microbial interaction with host immunity may better explain disease status and reveal appropriate individually tailored targets. Dietary probiotics reduce the incidence of ventilator-associated pneumonia, without impacting the duration of mechanical ventilation, length of hospitalization, or mortality [133]. This raises important questions of a potential to partly restore "diseased" respiratory microbiomes using microbiota-directed or host-targeted therapies such as probiotics and/or metabolite supplementation.…”
Section: Targeting Mucin In Pulmonary Infection and Diseasementioning
confidence: 99%
“…Probiotics are living micro-organisms which confer benefits to the host when administrated in adequate dose, and most used organisms include bifidobacteria, lactic acid bacteria, enterococci, and yeast (139). Probiotics usually have distinctive characteristics such as the ability of surviving under intestinal conditions, stimulating the immune system and acting against pathogens, also preventing health-care associated pneumonia (140). Furthermore, probiotics exert interesting properties by modulating cytokines production, interacting with TLRs, antagonizing pathogens in cell adhesion and mucin homeostasis, and by stimulating SCFAs production (141).…”
Section: Treatment Proposals Prebiotics and Probioticsmentioning
confidence: 99%